Egg Shell Quality and Bone Status as Affected by Environmental Temperature, Ca and Non-Phytate P Intake and in vitro Limestone Solubility in Single-Comb White Leghorn Hens - Zhang, Bingfan; Weil, Jordan; Guerra, Antonio Beita; Maharjan, Pramir; Hilton, Katie; Suesuttajit, Nawin; Patr, Diego Martinez Patino; Coon , Craig N. (International Journal of Poultry Science, 2020)
Background and Objective: Environmental temperature (ET) often changes the nutrient intake/output for layers. Changing feed formulations based on ET may need to be utilized to obtain optimum performance, shell quality and bone status. This study was conducted to investigate the effects of temperature, Ca intake, non-phytate P (NPP) intake and in vitro limestone solubility (LS) on egg-shell quality and bone status in commercial White Leghorn hens. Materials and Methods: Two 9 weeks feeding experiments were conducted with two ages of commercial White Leghorns housed in either a constant (21.1°C) thermoneutral temperature or in hot ambient temperatures (constant: 26.6°C or 32.2°C or cycling: 01:00-09:00 h at 26.7°C; 09:00-13:00 h at 29.4°C; 13:00-18:00 h at 35.0°C and 18:00-01:00 h at 29.4°C with 24 h mean of 29.7°C). In Experiment (EXP) 1, 360-130 week molted hens were housed in a constant ET at 21.1, 26.6 and 32.2°C and fed 3 levels of Ca (3.8 g, 4.9 g and 6 g h–1 day–1), 2 levels of NPP (450 and 600 mg h–1 day) while feeding 2 different LS (in vitro solubility of 34.1 and 48.4%). In EXP 2, 480-48 week old hens were housed in constant ET at 21.1°C or in cycling hot ET(with 24 h mean of 29.7°C: 01:00-09:00 h at 26.7°C; 09:00-13:00 h at 29.4°C; 13:00-18:00 h at 35.0°C and 18:00-01:00 h at 29.4°C) and fed 2 different LS (in vitro solubility of 34.1 and 48.4%) and four predicted intakes of NPP ( 250, 350, 450 and 550 mg h–1 day–1). Results: Egg mass and shell weight per unit surface area (SWUSA) decreased with increasing ET (p<0.05), especially when ET was 29.7°C (cycling mean ET)or a constant ET was 32.2°C. Feeding layers a low soluble larger particle size limestone instead of a highly soluble limestone produced beneficial effects for SWUSA at the thermoneutral ET (21.1°C) but the beneficial effect was less or disappeared when ET was ≥26.6°C in EXP 1 and 2. Feeding layers 245 and 353 mg NPP h–1 day–1 supported satisfactory bone status at 21.1°C, however layers housed at ≥30°C needed an additional intake of 50 mg NPP h–1 day–1 to support bone integrity. Results of EXP 1 and 2 indicates that ≥48 week old layers housed in thermoneutral or warmer ET require a minimum of ≥4.2 g Ca h–1 day–1 for maintaining optimum shell quality and bone integrity. Conclusion: Feeding low LS (34.1% in vitro solubility) improved egg shell quality only for hens housed in thermoneutral ET (21.1°C) and did not improve egg shell quality at higher ET (constant or cycling). Daily NPP intake of 245 and 353 mg h–1 day–1 supported optimum egg production and bone status at 21.1°C, respectively. A higher NPP and Ca intake may be required for bone status compared to egg production, especially in older hens.